Phytochemical and Profiling of Bioactive Compounds from Beneng Taro (Xanthosoma undipes) Using Chromatography-Spectrometry Method - Yuniarsih, Eko; Trisnawati, Desi; Saepudin, Aang Asep; Maulani, Tuti Rostianti; Rahmawati, Dian Suci; Lanita; Jufrinaldi; Indrawati, Wiwik (Indonesian Journal of Applied Research (IJAR), 2026)
Beneng taro (Xanthosoma undipes K. Koch) was one of the local taro varieties originating from Pandeglang, Banten, characterized by its yellow color and potential as a source of bioactive components. This study aimed to identify bioactive components in the form of secondary metabolite profiles in Beneng taro using liquid chromatography–tandem mass spectrometry (LC MS/MS) and to evaluate its antioxidant activity. The study consisted of several stages, namely sample preparation, extraction using ethanol and aquadest solvents, and characterization, including the determination of total flavonoid and phenolic contents, antioxidant activity using the DPPH method, and LC MS/MS profiling. The Beneng taro extract obtained using ethanol contained total flavonoids and phenolics of 34.64 mg QE/g and 3.78 mg GAE/g, respectively, which were higher than those of the aquadest extract, with total flavonoid and phenolic contents of 1.92 mg QE/g and 2.14 mg GAE/g, respectively. Antioxidant activity analysis showed that the ethanol extract exhibited stronger activity than the aquadest extract, with IC₅₀ values of 197.2 ppm and 227.5 ppm, respectively. LC-MS/MS profiling revealed 20 compounds in the ethanol extract and 15 compounds in the aquadest extract, which potentially possessed antibacterial, antioxidant, anticancer, and antidiabetic activities. These results suggested that Beneng taro had potential for development as an ingredient in food products.